LISTENING ANXIETY AMONG INDONESIAN EFL STUDENTS - Vina Agustiana (University of Kuningan, 2019)
Listening skill is essential in EFL learning. Experiencing more than three years in teaching Listening, the researcher covers that EFL students face problems in comprehending what people say in target language. Through this study, the researcher aims at exploring EFL students’ experience in learning to listen to spoken English text which covers (a) students’ attitude towards learning to listen to spoken English texts, b) listening anxiety in listening to spoken English texts, and (c) students’ effort in improving their listening skill in listening to spoken English text. To meet the research objectives, the researcher used a quantitative research through applying a survey design. A closed ended questionnaire containing 50 questions were distributed to 58 EFL students of a Private University in West Java, Indonesia. The questionnaire was tested its validity and reliability. Moreover, the data were analyzed descriptive statistically. Data revealed that students show (a) a positive attitude towards learning to listen to English spoken text (3.56); (b) students’ listening anxiety is in high level (3.52); and (c) students have a high effort in improving their listening skill (3.74). To conclude with, in spite of the high level of students’ listening anxiety, they show the high level of attitude in learning to listen to English spoken text and the high effort in improving their listening skill as well.Keywords: attitude; listening anxiety; listening skill.